2012
DOI: 10.1111/j.2047-6310.2012.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental anthropometrics, early growth and the risk of overweight in pre‐school children: the Generation R Study

Abstract: Maternal and paternal anthropometrics affect early growth in pre-school children differently. Gestational weight gain in mothers without overweight and obesity is related to the risk of overweight in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 46 publications
(62 reference statements)
4
35
2
Order By: Relevance
“…This finding is consistently reported by other studies (Durmuş et al, 2013;Sijtsma, Sauer, & Corpeleijn, 2015), which reveal that the maternal body mass index had a stronger effect on the body mass index of preschool children than the paternal body mass index did. An analysis of the relationship between obesity in preschool children and their parents is important because parental obesity more than triples the risk of adult obesity among both obese and non-obese pre-schoolers (Whitaker et al, 1997).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is consistently reported by other studies (Durmuş et al, 2013;Sijtsma, Sauer, & Corpeleijn, 2015), which reveal that the maternal body mass index had a stronger effect on the body mass index of preschool children than the paternal body mass index did. An analysis of the relationship between obesity in preschool children and their parents is important because parental obesity more than triples the risk of adult obesity among both obese and non-obese pre-schoolers (Whitaker et al, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…The worldwide prevalence of overweight/obesity among preschool children increased from 4.2% in 1990 to 6.7% in 2010, with the expected representation of overweight/obesity accounting for 9.1% or ≈60 million in 2020, and the estimate is even higher (14.1%) in developed countries (de Onis, Blössner, & Borghi, 2010), despite the differences in the prevalence of overweight/obesity among pre-schoolers from different continents and countries (de Onis et al, 2010; include parental obesity (Parikka et al, 2015;Whitaker et al, 1997), especially in mothers (Durmuş et al, 2013;Kitsantas & Gaffney, 2010), or both parents being obese (Durmuş et al, 2013;Parikka et al, 2015), high birth weight of children (Kitsantas & Gaffney, 2010), non-married mothers belonging to low socioeconomic groups (Kitsantas & Gaffney, 2010), low levels of education of parents (Parikka et al, 2015), low levels of physical activity (PA), and excessive television viewing (Mendoza, Zimmerman, & Christakis, 2007;te Velde et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…1,2,30,31 These studies are limited by the use of self-reported height and weight. 3,31 In addition, many studies focus on child weight status during ages 4 to 11 years, 3,31,32 often missing the critical time period from birth to age 5 years.…”
Section: Discussionmentioning
confidence: 98%
“…C HILDREN WITH AT LEAST ONE OVERWEIGHT OR obese parent are at higher risk for becoming obese or overweight themselves compared with children with normal-weight parents, even as early as age 4 years. 1,2 One Australian study among school-aged children found that having an overweight or obese father and a normal-weight mother increased the child's likelihood for being overweight by four times. 3 However, the reverse scenario in which the father was normal weight and the mother was overweight or obese was not a significant predictor of child weight.…”
mentioning
confidence: 98%
“…Stronger associations for maternal BMI suggest direct intrauterine mechanisms, whereas similar or stronger associations for paternal BMI suggest a role for shared genetic or family-based, lifestyle-related characteristics [12] . Stronger associations of maternal pre-pregnancy BMI with birth weight have been reported than for paternal BMI [67] . Although studies comparing associations of maternal and paternal BMI with childhood BMI have shown conflicting results [68] , studies examining these associations with more detailed childhood fat mass measures and other cardio-metabolic risk factors have shown that maternal pre-pregnancy BMI tends to be more strongly associated with childhood total fat mass, android/gynoid fat mass ratio and clustering of cardiometabolic risk factors than paternal BMI [34,69] .…”
Section: Causality or Confoundingmentioning
confidence: 99%